Physiological Comparison of l-Serine Dehydratase and Tryptophanase from Bacillus alvei - Griffiths, S. K. (1970)
Tryptophanase from Bacillus alvei also possesses serine dehydratase activity. A comparison of this enzyme with l-serine dehydratase [l-serine hydro-lyase (deaminating), EC 4.2.1.13] in toluene-treated whole cell preparations of the organism was undertaken. Tryptophanase is a constitutive enzyme in B. alvei. The dehydratase undergoes a repression-derepression-repression sequence as the l-serine level in the growth medium is increased from 0 to 0.1 m. Tryptophanase activity is decreased in organisms grown in medium containing glucose. Both enzymes are repressed in organisms grown in glycerol-containing medium. l-Serine dehydratase has a pH optimum of 7.5 in potassium phosphate buffer; tryptophanase functions optimally in this buffer at pH 8.2. Both enzymes lose activity in the presence of tris(hydroxymethyl)aminomethane buffer. Either K(+) or NH(4)(+) is required for full tryptophanase activity, but Na(+) is markedly inhibitory. These three cations are stimulatory to l-serine dehydratase activity. Both enzymes are subject to apparent substrate inhibition at high concentrations of their respective amino acids, but the inhibition of tryptophanase activity can be completely overcome by the removal of indole as it is formed. The dehydratase does not catalyze cleavage of d-serine, l-threonine, or α-substituted serine analogues at the concentrations tested. However, activity of the enzyme in cleaving l-serine is competitively inhibited by d-serine, indicating that the d-isomer can occupy an active site on the enzyme. The enzyme catalyzes cleavage of some β-substituted serine analogues.